Three-dimensional dipole momentum analog based on L-shape metasurface - Li, Tianyou; Chen, Yanjie; Wang, Yongtian; Zentgraf, Thomas; Huang, Lingling (Applied physics letters, 2023)
The achievement of a flat metasurface has realized extraordinary control over light–matter interaction at the nanoscale, enabling widespread use in imaging, holography, and biophotonics. However, three-dimensional metasurfaces with the potential to provide additional light–matter manipulation flexibility attract only little interest. Here, we demonstrate a three-dimensional metasurface scheme capable of providing dual phase control through out-of-plane plasmonic resonance of L-shape antennas. Under circularly polarized excitation at a specific wavelength, the L-shape antennas with rotating orientation angle act as spatially variant three-dimensional tilted dipoles and are able to generate desire phase delay for different polarization components. Generalized Snell's law is achieved for both in-plane and out-of-plane dipole components through arranging such L-shape antennas into arrays. These three-dimensional metasurfaces suggest a route for wavefront modulation and a variety of nanophotonic applications.